Digital design and fabrication of controlled porosity, personalized lower limb AFO splints (Transactions on Additive Manufacturing Meets Medicine, 2020)
We present the preliminary phases of developing a custom lower limb splint concept which considers both design and mechanical elements of the final device. We present an approach to verify the flexural properties of the device through the systematic measurement of flexural stress of 3D printed samples and how this evolves based upon increased porosity. Our initial results demonstrate we can effectively predict the stiffness characteristics of a 3D printed splint concept and apply this to inform the design choices.
Keywords: printed splint